KELAHIRAN SUBJEK SUNDA Genealogi Subjek dan Kewilayahan Kelompok Etnis Sunda - , Holy Rafika Dhona ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research tries to look at the construction of the subject of Sunda as particle effect of colonialism. Analyzing the discourses on Sundanese, mainly the text of Papaes Nonoman, a newspaper published by Paguyuban Pasundan (1914-1919), this research asks three main questions i.e